Evaluation of the Impact of the Food Brigade Program on the Financial Performance of Rice Farming in Sambas Regency - Suleman Arison Rajagukguk (Universitas Galuh, 2026)
Food security has become a strategic national issue that requires policies based on efficiency and productivity improvement. The Food Brigade Program is an initiative of the Ministry of Agriculture aimed at strengthening rice farming through mechanization, collective land management, and support for modern technology. This study aims to evaluate the impact of the program on the financial performance of rice farming in Sambas Regency, a region with the largest number of Food Brigade groups in West Kalimantan. The research employed a quantitative approach with a population consisting of all members of 80 Food Brigade groups and 30 non-participating Food Brigade farmer groups, who were selected as respondents through a census technique. Primary data were collected through questionnaires, interviews, and field observations, while secondary data were obtained from reports of relevant institutions. The analysis included the calculation of production costs (Total Cost), revenue (Total Revenue), net income, Revenue-Cost Ratio (R/C Ratio), and Break-Even Point (BEP). In addition, performance was evaluated using the Balanced Scorecard, which encompasses financial, customer, internal process, and learning and growth perspectives.The results of the study are expected to show the extent to which the Food Brigade Program reduces production costs, improves efficiency, and strengthens the profitability of rice farming. The findings are also expected to serve as a basis for evidence-based policy recommendations for the development of sustainable agricultural programs in Indonesia.